SOCIAL PROBLEMS AND PSYCHOLOGICAL APPROACHES - Omondullayev Jamoliddin Xoshimjon o‘g‘li; Toshpulatov Ibrohim Ikromjonovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
This article examines social problems and the role of psychological approaches in solving them. Social problems, including unemployment, education problems, health care, and crime, are considered. Methods for solving these problems through psychological approaches, including cognitive, behavioral, and emotional approaches, are analyzed. The effectiveness of psychological approaches in solving social problems is shown based on the ideas and research of Uzbek scientists.